Innovative Microorganisms in Environmental Cleanup: Effective Microorganism-Based Bioprocesses - Hakan Çelebi; Tolga Bahadır; İsmail Şimşek; Şevket Tulun (Biology and Life Sciences Forum)
All over the world, environmental engineers, environmental biologists, biochemists, and other scientists are concerned about environmental pollution. In particular, different treatment technologies and applications in terms of water and soil health have been investigated for years. Studies show that the bioprocess (biosorption, bioremediation, bioaccumulation, etc.) approach is more advantageous (economical, easy design, and environmentally friendly, etc.) than many treatment methods. Thanks to these advantages, bioprocesses have been preferred for the removal of different pollutants in the receiving environment. Effective microorganisms (EMOs) are defined as mixed cultures of advantageous and naturally occurring microorganisms that can be used as vaccine material. An EMO is a natural fermentation product that is not chemically or genetically modified in the form of a concentrated solution. An EMO consists of 10 species, including photosynthetic (Rhodopseudomonas palustrus and Rhodobacter spaeroides, etc.) and lactic acid (Lactobacillus plantarum, Lactobacillus casei and Streptoccus lactis, etc.) bacterial groups, yeasts (Saccharomyces cerevisiae and Candida utilis, etc.), actinomycetes, and fermenting fungi The main components of an EMO are lactic acid bacteria, yeasts, and photosynthetic bacteria. In a liquid solution, they are in harmony. This article aims to review the literature on “Effective Microorganisms (EMOs)” from different scientific databases and discuss the effectiveness of using EMOs for bioprocess.